VARIATIONS IN HAEMATOLOGICAL FACTORS OF GUINEA PIGS INFECTED AND TREATED WITH DIFFERENT ANTI SCHISTOSOMA THERAPY (FUDMA JOURNAL OF SCIENCES, 2023)
A study was conducted to examine some variation in haematological standards on Guinea pigs experimentally infected with Schistosoma haematobium. Male and female guinea pigs weighing 2.5–6.5 kg were divided into four groups, which were further divided into three replicates with control. The groups were infected with S. haematobium and allow for space of 2, 7, 8 and 90 days post infection. Blood sample for White Blood Cell count (WBC), Park Cell Volume (PCV)and Haemoglobin (HBC) determination was collected using orbital technique from the retrobulbar plexus of the medial canthus of the eye of the guinea pigs, before analysis. The value of white blood cell count on guinea pigs treated with praziquantel two days before and after treatment were not significant 0.0605 (P > 0.05), artemether before and after treatment were statistically significant 0.0163 (P < 0.05) while artequine pre and post treatment were not significant 0.0539. Actions of praziquantel, artemether artequine and praziquantel/artequine on pack cell volume decreases after treatment (t-Test, P < 0.01) two days post treatment. The mean level of PCV seven and twenty eight day’s pre and post treatment in the entire drug administered was highly significant (t-Test, P < 0.01). The t statistics obtained shows that the mean value of HBC in all the treatment groups as the parasite develops (2-7-28-90 days) were significant (P < 0.01; P < 0.05).
Keywords: S. haematobium, Heamatological, Praziquantel, Artequine